Stability of the Microbiome of the Sponge Mycale (Oxymycale) acerata in the Western Antarctic Peninsula - Happel, Lea; Rondon, Rodolfo; Font, Alejandro; González-Aravena, Marcelo; Cárdenas, César A. (Frontiers in Microbiology, 2022)
The sponge microbiome, especially in Low Microbial Abundance (LMA) species, is expected to be influenced by the local environment; however, contrasting results exist with evidence showing that host specificity is also important, hence suggesting that the microbiome is influenced by host-specific and environmental factors. Despite sponges being important members of Southern Ocean benthic communities, their relationships with the microbial communities they host remain poorly studied. Here, we studied the spatial and temporal patterns of the microbiota associated with the ecologically important LMA sponge M. acerata at sites along ∼400 km of the Western Antarctic Peninsula (WAP) to assess patterns in the core and variable microbial components of the symbiont communities of this sponge species. The analyses of 31 samples revealed that the microbiome of M. acerata is composed of 35 prokaryotic phyla (3 Archaea, 31 Bacteria, and one unaffiliated), being mainly dominated by Proteobacteria with Gammaproteobacteria as the most dominant class. The core community was composed of six prokaryotic OTUs, with gammaproteobacterial OTU (EC94 Family), showing a mean abundance over 65% of the total abundance. Despite some differences in rare OTUs, the core community did not show clear patterns in diversity and abundance associated with specific sites/environmental conditions, confirming a low variability in community structure of this species along the WAP. The analysis at small scale (Doumer Island, Palmer Archipelago) showed no differences in space and time in the microbiome M. acerata collected at sites around the island, sampled in three consecutive years (2016–2018). Our results highlight the existence of a low spatial and temporal variability in the microbiome of M. acerata, supporting previous suggestions based on limited studies on this and other Antarctic sponges.